Identifikasi Profil Metabolit Sekunder Subfraksi Teraktif Daging Buah Kepundung (Baccaurea racemosa) menggunakan High Resolution Mass Spectrometry - Cici Okta Maelina; Lina Permatasari (Sinteza, 2025)
Baccaurea racemosa (kepundung) is a tropical plant with potential as a source of bioactive compounds. This study aimed to identify the secondary metabolite profile of the most active subfraction of kepundung fruit pulp using High Resolution Mass Spectrometry (HRMS). MS analysis was performed with Heated Electrospray Ionization (H-ESI) positive ionization mode. Compound identification was performed using Thermo Scientific™ software. HRMS analysis revealed the presence of 1,149 compounds, with the ten most abundant being L-pyroglutamic acid, senkyunolide H, trans-acotinic acid, glutarate, zerumbone, choline, cuminaldehyde, D-(+)-camphor, N-methyl-2-pyrrolidone, and nicotinic acid. These compounds have been reported to have pharmacological activities, especially as antimicrobial and antifungal agents. These findings support the potential use of kepundung fruit pulp as a promising natural source for phytopharmaceutical development.